2014
DOI: 10.1016/j.bse.2014.06.004
|View full text |Cite
|
Sign up to set email alerts
|

When physical oceanography meets population genetics: The case study of the genetic/evolutionary discontinuity in the endangered goliath grouper (Epinephelus itajara; Perciformes: Epinephelidae) with comments on the conservation of the species

Abstract: Epinephelus itajara is one of the marine fish species most threatened for extinction and it is considered to be "critically endangered" by the IUCN. The present study evaluated the genetic diversity of the species and the genetic/evolutionary relationships of its populations along the Atlantic coast of South America. The results indicate relatively reduced genetic variation, re-emphasizing the low adaptive potential of the species. One of the populations presented relatively high degrees of genetic diversity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 41 publications
1
11
2
3
Order By: Relevance
“…Despite the small sample size for the southernmost population, at Babitonga (Santa Catarina) the common haplotypes are shared with other population units; this population is not isolated from the others and is characterized by reduced genetic diversity. This finding differs from that of Benevides et al (2014), who used a nuclear marker. This incongruent evidence might suggest possible phenomena of sex-biased demography such as male/ female phylopatry in the region.…”
Section: Population Structuringcontrasting
confidence: 97%
See 3 more Smart Citations
“…Despite the small sample size for the southernmost population, at Babitonga (Santa Catarina) the common haplotypes are shared with other population units; this population is not isolated from the others and is characterized by reduced genetic diversity. This finding differs from that of Benevides et al (2014), who used a nuclear marker. This incongruent evidence might suggest possible phenomena of sex-biased demography such as male/ female phylopatry in the region.…”
Section: Population Structuringcontrasting
confidence: 97%
“…Torres et al (2013) developed a molecular identification protocol for monitoring the fishing of groupers, including E. itajara, E. morio, Mycteroperca bonaci and M. marginata. Using simple repeat sequence markers, Benevides et al (2014) confirmed the low degree of genetic variation in E. itajara populations from ten locations, including the Atlantic coast of South America, and revealed a strong population division in southern Brazil in comparison with populations found in the eastern and northern regions of the country. Silva-Oliveira et al (2008) used a mitochondrial marker to study E. itajara populations on the northern coast of Brazil, while Benevides et al (2014) used a nuclear marker to study populations on the northern and eastern coasts.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…Several dynamic factors such as river discharge volume, coastal currents and surface wind may or may not act as a barrier to the displacement of the larvae and establishment of different populations. Despite the lack of clear evidence regarding coastal current dynamics along the coast of South America affecting P. pagrus, previous studies on other species have suggested the role of ocean currents in modeling the genetic structure by promoting specific local larval retention (Benevides et al, 2014).…”
Section: Discussionmentioning
confidence: 99%